Project Camelot: A U.S. Army Social Science Research Project - Sztankai, Krisztián (Academic and Applied Research in Military and Public Management Science, 2024)
Project Camelot was an ambitious social science project that came into existence in late 1964. The goal of the project was to assess the causes of war and to identify the actions that the American government could take to prevent such wars. The period between the introduction of Project Camelot and its ultimate demise raises interesting questions about the relationship between the American government, the military, and social sciences.